The purpose of homecoming / Valerien Corinthina Clement - Clement, Valerien Corinthina (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Homecoming is so named because graduates return "home" to their university to participate in various activities including dances and class reunions. Homecoming involves a variety of activities. The concept of inviting back former members or graduates of an organisation to commemorate the existence of the group is known as a "homecoming". Whether they are in high school or university, many students' favourite period of the academic year is homecoming. How come homecoming is such a huge deal though?